Retrograde recanalization of chronic coronary occlusion - S.М. Furkalo (Кардіохірургія та інтервенційна кардіологія)
Chronic coronary occlusion (сhronic total occlusion – CТO) is fixed at 1 in 5 patients who underwent cardiac catheterization. Recanalization of chronic coronary occlusions is one of the most technically difficult interventional procedures. Successful recanalization of CТO is associated with better survival compared to patients where the procedure of recanalization was not successful. Thus, potential candidates for retrograde recanalization of CТO are рatients after failed attempt of recanalization with clear indications and motivated to implement PCI; with refractory angina and CТO of native coronary arteries after CABG; single-vessel coronary artery disease (right coronary artery, RCA or left anterior disease, LAD) with preserved left ventricular function and preserved kidney; patients with multivessel disease and related comorbidity making coronary artery bypass surgery impossible. Since 2007, 102 retrograde recanalizations of CТO were performed with total efficiency 64.3 %. CТO interventions were most often used in LAD – 50 %, RCA – 41.7 %, and left circumflex artery, LCx – 8.3 % cases. It was a successful method in CТO cases of RCA – in 86.6 % of cases, LAD – in 66 % of patients; in case of LCx CТO recanalization was successful in only two patients. Septal collaterals with retrograde approach were used in most cases – 88 patients, epicardial collaterals – in 12 cases. coronary bypass was used for retrograde access in one case, venous bypass to the LAD – in one case as well. The efficacy of retrograde approach during last five years ranged from 60 to 80 %.